ANALISIS PROGRAM STIMULASI DETEKSI INTERVENSI DINI TUMBUH KEMBANG BALITA DI PUSKESMAS PADANG SIBUSUK : deteksi dini - Wahyuni; yulia yesti; Husri Yanti (LLDIKTI Wilayah X, 2022)
ABSTRACT Comprehensive and quality programs for fostering children's growth and development in toddlerhood are one of the Stimulation, Detection and Early Intervention Programs for Growth and Development (SDIDTK). In 2021 at the Padang Sibusuk health center the achievements of the SDIDTK toddler program are still below the target (55.89%). The purpose of this study was to analyze the SDIDTK toddler program at the Padang Sibusuk Health Center in 2021. Qualitative research methods using in-depth interview techniques, document review and observation. Selection of research informants with purposive sampling. The components studied are the input, process and output of the SDIDTK program. The results of the study found that for the input component there was no specific policy issued by the local government regarding the SDIDTK program. The regulations have not been disseminated to all related networks, the human resources managing and implementing the SDIDTK program are sufficient in quantity but inadequate in quality. Funds, facilities and infrastructure are not sufficient. The components of the planning and organizing process already exist, but the support across programs and sectors has not been maximized. SDIDTK Monitoring and evaluation implementation has not been maximized. The SDIDTK program achievement output component has not been successful.